THE REE SYSTEMATICS OF UPPER ARCHEAN SEDIMENTARY ASSEMBLAGES IN CENTRAL KARELIA - Svetov S.A.; Svetova A.I. (My University, 2004)
Geochemical composition of sedimentary assemblages is determined by the interaction of specifics of provenances, weathering conditions, mass transfer, sedimentation, metamorphism, and other factors. The role of geodynamic setting of provenances is crucial for the composition of sedimentary (mainly terrigenous) assemblages [1].Therefore, their chemistry is a reliable indicator of the paleogeodynamic setting [2–6]. Lithogeochemical studies of terrigenous associations of young (<2.9 Ga) greenstone structures of western Karelia (Kostomuksha and Hizovaara) [7, 8] provided new information on the evolution of the sedimen-tation regime and geodynamic setting of these structures. However, no lithogeochemical investigations have been carried out for the older greenstone domains of the Karelian Craton. We present new geochemical data on the REE systematics of sedimen-tary assemblages distinguished in the stratotype section of the Hautavaara–Koikary test site in the Upper Archean (3.05–2.85 Ga) Vedlozero–Segozero green-stone belt of central Karelia. The greenstone belt located in the southeastern part of the Fennoscandian Shield extends over ~300 km in the N–S direction at a width of 50–60 km and consists of several local domains (Hautavaara, Koikary, Pala-selga, Sovdozero, and others) [9, 10]. Geodynamic reconstructions [11] allowed us to distinguish mag-matic systems related to the ancient (3.05–2.95 Ga) island arc [12], back-arc basin (3.05–2.95 Ga), and young (2.90–2.85 Ga) volcanic arc, which are consistent with formation of greenstone belt as convergent protoocean–protocontinent zone between microplates.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей